Clinical outcomes and genomic profiles of MAP2K1-mutated primary cutaneous melanocytic tumoursResearch in context - Chiel F. Ebbelaar; Anne M.L. Jansen; Leonie C.M. Speet; Frans Schutgens; Sietske Zoetemeyer; Anne-Marie Cleton-Jansen; Marijke R. van Dijk; Gerben E. Breimer; Lourens T. Bloem; Wendy W.J. de Leng; Remco van Doorn; Karijn P.M. Suijkerbuijk; et al. (EBioMedicine)
Summary: Background: Primary cutaneous melanocytic tumours harbouring MAP2K1 mutations without second-hit genomic alterations represent a subclass of neoplasms with poorly understood biological behaviour. This study aimed to investigate the clinical outcomes and genomic characteristics of these tumours. Methods: This cohort study included primary cutaneous melanocytic tumours with MAP2K1 mutations from patients at two academic centres (Leiden University Medical Centre and University Medical Centre Utrecht). These mutations were categorised into three functional classes: Class I (RAF-dependent), Class II (RAF-regulated), and Class III (RAF-independent). Tumours underwent histopathological evaluation, next-generation sequencing (NGS), and copy number variation (CNV) analysis and were categorised as non-melanoma or melanoma. Clinical outcomes were assessed for each mutation class during follow-up visits and through the Dutch Pathology Database (PALGA) using the composite outcome of metastatic melanoma (recurrence, metastasis, or melanoma-related death). Findings: A total of 102 patients were included, with tumours classified as melanoma in 52 (51%) and non-melanoma in 50 (49%). The tumours displayed spitzoid histomorphology in over two-thirds of cases and harboured 31 distinct MAP2K1 mutations: 20 Class I (19.6%), 56 Class II (54.9%), and 26 Class III (25.5%). Class I mutations exclusively co-occurred with BRAF or NRAS mutations, while Class II and III mutations often acted as sole tumour drivers. Of the tumours with Class I mutations, 95% were classified as melanoma, which was less frequently the case for Class II (risk ratio [RR] 0.43 [95% CI: 0.31–0.60], p < 0.001) and Class III mutations (RR 0.40 [95% CI: 0.25–0.67], p < 0.001). MAP2K1 mutation Class and TERT-p mutation status were independent predictors for the composite outcome. Compared to Class I mutations, Class II mutations were negatively associated with the composite outcome (odds ratio [OR] 0.16 [95% CI: 0.03–0.75], p = 0.03), whereas Class III mutations were not associated (OR 0.31 [95% CI: 0.05–1.54], p = 0.16). TERT-p mutations were positively associated with the composite outcome (OR 23.1, 95% CI: 3.99–439.8, p < 0.005). Interpretation: Class I MAP2K1 mutations typically occur alongside other MAPK pathway mutations and may contribute to aggressive melanoma behaviour. In contrast, Class II and III MAP2K1 mutations can independently drive melanocytic tumourigenesis with a potential for metastasis, aligning with conventional melanomagenesis pathways, despite their frequent spitzoid histomorphology. Funding: This research was supported by the Hanarth Fund.